High-performance pseudo-capacitor energy storage device based on a hollow-structured copper sulfide nanoflower and carbon quantum dot nanocomposite. (1st September 2020) - Quan, Yiling; Wang, Guoxiang; Lu, Lu; Wang, Zhixin; Xu, Hongfeng; Liu, Sa; Wang, Dazhi
Abstract: Transition metal sulfides are widely used in high-performance energy storage equipment due to its excellent electrochemical activity and electrical conductivity. In this study, we introduce a carbon quantum dot (CQD)-doped hollow CuS composite (CuS@CQDs) as a novel electrode material for advanced asymmetric supercapacitors through one-step solvothermal synthesis and an impregnation bonding method. The CuS@CQDs composites with uniform and hierarchical porous architecture possess high specific area and low specific resistance, which can facilitate the transport of electrolytes and electrons. The as-prepared CuS@CQDs-ICM electrode exhibits a maximum specific capacitance of 920.5 F g −1 at a current density of 0.5 A g −1 and an energy density of 44.19 W h kg −1 at a power density of 397.75 W kg −1 with an excellent cycling stability of 92.8% after 10, 000 cycles. The satisfactory electrochemical performance can be attributed to the unique nanoflower-like hollow structure of the CuS@CQDs composites and the synergy between CuS and CQDs.